Transformation of Sufi Spirituality-Based Dawar Practices in Dance Communities in Contemporary Indonesia - Alvin Noor Sahab Rizal; M. Rais Ribha Rifqi Hakim; Ayna Jamila Salsabila (SUHU: Journal of Sufism and Humanities, 2026)
The growing presence of Sufi dance communities across Indonesia reflects a public search for religious communication that is gentle, reflective, and grounded in experiential spirituality. Da‘wah practices that once relied primarily on verbal preaching have shifted toward performative-aesthetic approaches in which rotational movement, rhythmic remembrance, and interpretations of Jalaluddin Rumi’s poetry serve as vehicles for internalizing spiritual values. Objective: This study aims to examine the transformation of Sufi dance into a contemporary medium of Islamic da‘wah in Indonesia and to analyze its spiritual, communicative, and socio-cultural functions. Method: The study employs a library research methodology by systematically reviewing national and international literature on Sufism, performance studies, cultural da‘wah, and contemporary Sufi dance communities in Indonesia. Results: The findings reveal that Sufi dance functions as an alternative model of da‘wah that integrates aesthetic expression, spiritual practice, and social interaction. The localization of Mevlevi traditions has enabled Sufi dance to reach broader audiences, including women and younger generations, while digital media has significantly expanded its dissemination. At the same time, the increasing circulation of Sufi dance through digital platforms has created a tendency for performances to be appreciated primarily as visual spectacles, thereby reducing their spiritual substance. Conclusion: The study concludes that Sufi dance represents a relevant form of contemporary Islamic da‘wah that combines artistic performance with spiritual communication. Beyond preserving Sufi traditions, it offers an inclusive and emotionally engaging approach to religious outreach, contributing to spiritual development and social cohesion within contemporary Indonesian society.